Antibacterial siderophores of pandoraea pathogens and their impact on the diseased lung microbiota - Herzog, Elena; Ishida, Keishi; Scherlach, Kirstin; Chen, Xiuqiang; Bartels, Benjamin; Niehs, Sarah P.; Cheaib, Bachar; Panagiotou, Gianni; Hertweck, Christian (Angewandte Chemie. International edition, 2025)
Antibiotic-resistant bacteria of the genus Pandoraea, frequently acquired from the environment, are an emerging cause of opportunistic respiratory infections, especially in cystic fibrosis (CF) patients. However, their specialized metabolites, including niche and virulence factors, remained unknown. Through genome mining of environmental and clinical isolates of diverse Pandoraea species, we identified a highly conserved biosynthesis gene cluster (pan) that codes for a nonribosomal peptide synthetase (NRPS) assembling a new siderophore. Using bioinformatics-guided metabolic profiling of wild type and a targeted null mutant, we discovered the corresponding metabolites, pandorabactin A and B. Their structures and chelate (gallium) complexes were elucidated by a combination of chemical degradation, derivatization, NMR, and MS analysis. Metagenomics and bioinformatics of sputum samples of CF patients indicated that the presence of the pan gene locus correlates with the prevalence of specific bacteria in the lung microbiome. Bioassays and mass spectrometry imaging showed that pandorabactins have antibacterial activities against various lung pathogens (Pseudomonas, Mycobacterium, and Stenotrophomonas) through depleting iron in the competitors. Taken together, these findings offer first insight into niche factors of Pandoraea and indicate that pandorabactins shape the diseased lung microbiota through the competition for iron.